2019
DOI: 10.2147/ott.s202933
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effective high intensity focused ultrasound treatment in recurrent aggressive breast fibromatosis: a case report</p>

Abstract: Aggressive breast fibromatosis (referred to as a desmoid tumor) is a rare, locally invasive, non-metastasizing tumor with high recurrence rate. The therapeutic modalities range from surgery and radiotherapy to medical treatments. However, the optimal treatment is controversial, especially in a situation of repeated recurrence. Here, we present a case of a patient with aggressive breast fibromatosis with multiple recurrence after surgeries, who underwent high intensity focused ultrasound (HIFU) treatment effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Our previous study showed that low power cumulative HIFU treatment showed benefit both in survival and safety in locally advanced pancreatic cancer and recurrent aggressive breast fibromatosis. 14,16 Here, we presented a case of myxofibrosarcoma in right upper arm with multiple recurrence after surgeries. The patient was a young woman with recurrence only 7 months after surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous study showed that low power cumulative HIFU treatment showed benefit both in survival and safety in locally advanced pancreatic cancer and recurrent aggressive breast fibromatosis. 14,16 Here, we presented a case of myxofibrosarcoma in right upper arm with multiple recurrence after surgeries. The patient was a young woman with recurrence only 7 months after surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Under general anesthesia, patients receive low power and prolonged treatment time, so that the heat accumulates evenly and slowly in target tissue and causes the tumor coagulative necrosis eventually. Our previous study showed that low power cumulative HIFU treatment showed benefit both in survival and safety in locally advanced pancreatic cancer and recurrent aggressive breast fibromatosis 14,16 …”
Section: Discussionmentioning
confidence: 99%
“…The FEP-BY02 high-intensity focused ultrasound tumor treatment system (Yuande Biomedical Engineering Co. Ltd, Beijing, China) was used, and the HIFU procedure was performed by Hu et al. [ 13 ] in this case. During the operation, a pulsed heat accumulation approach was applied to dynamically modulate the therapeutic area, intensity and dose based on the intraoperative ultrasound contrast imaging.…”
Section: Case Reportmentioning
confidence: 99%
“…The watch-and-wait policy is recommended by NCCN 2018 guidelines where observation applies to selected patients in non-life-threatening situations. However, it is confusing to judge the criterion for ‘selected patients’, and Zhao et al ( 40 ) believes that surgery should be performed once the disease has progressed. Others believe that the endpoint of this type of modality depends on the patient's symptoms, medical status and the biological properties of the tumor ( 41 ).…”
Section: Surgery and Watch And Waitmentioning
confidence: 99%
“…Several studies have illuminated the efficacy of HIFU treatment on desmoid tumors. Zhao et al ( 40 ) reported the first case of HIFU treatment in aggressive breast fibromatosis with multiple recurrence following surgery. Ghanouni et al ( 96 ) applied HIFU treatment to 15 selected patients with extra-abdominal desmoids.…”
Section: Hifumentioning
confidence: 99%